2008
DOI: 10.1007/s10549-008-9964-x
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression of topoisomerase II alpha (TOP2A) by microarray analysis is highly prognostic in estrogen receptor (ER) positive breast cancer

Abstract: Introduction Overexpression of Topoisomerase II alpha (TOP2A) has been implicated with gene amplification of the 17q21 amplicon and consecutively with ErbB2 overexpression and amplification. However, gene amplification does not necessarily correlate with RNA and protein expression. There is growing evidence that TOP2A protein expression is a strong prognostic and TOP2A gene amplification might be a predictive marker (particularly for the use of anthracyclines). Methods Large scale analysis was performed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
47
3
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 37 publications
(45 reference statements)
3
47
3
1
Order By: Relevance
“…The genes were chosen from literature review on the basis of their being identified as (i) possible prognostic factors in residual disease at protein (4,(6)(7)(8)(9)(10) or mRNA level (11), (ii) as significantly up-or downregulated, but of unknown prognostic value in residual disease (12)(13)(14)(15)(16)(17)(18)(19)(20), (iii) as predictive of chemotherapy resistance (6,11,16,19,(21)(22)(23)(24)(25)(26)(27)(28)(29), and/or (iv) identified as possible prognostic factors over several previous datasets (26,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). In addition to the previously established prognostic factors ESR1 and ERBB2, the genes were also chosen to represent different pathways and biological processes of known implication in tumor progression or response to therapy, such as stemcellness (ALDH1A1, CD44, and STAT3), proliferation (TOP2A, MKI67, and AURKA), apoptosis (BCL2, BCL2L1, and PAWR), immunologic response (CD3D, CXCL13, and STAT1), epithelial-to-mesenchymal transition (EMT; SNAI1, SNAI2, SOX9, and TWIST), stromal activation (DECORIN, ...…”
Section: Introductionmentioning
confidence: 99%
“…The genes were chosen from literature review on the basis of their being identified as (i) possible prognostic factors in residual disease at protein (4,(6)(7)(8)(9)(10) or mRNA level (11), (ii) as significantly up-or downregulated, but of unknown prognostic value in residual disease (12)(13)(14)(15)(16)(17)(18)(19)(20), (iii) as predictive of chemotherapy resistance (6,11,16,19,(21)(22)(23)(24)(25)(26)(27)(28)(29), and/or (iv) identified as possible prognostic factors over several previous datasets (26,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). In addition to the previously established prognostic factors ESR1 and ERBB2, the genes were also chosen to represent different pathways and biological processes of known implication in tumor progression or response to therapy, such as stemcellness (ALDH1A1, CD44, and STAT3), proliferation (TOP2A, MKI67, and AURKA), apoptosis (BCL2, BCL2L1, and PAWR), immunologic response (CD3D, CXCL13, and STAT1), epithelial-to-mesenchymal transition (EMT; SNAI1, SNAI2, SOX9, and TWIST), stromal activation (DECORIN, ...…”
Section: Introductionmentioning
confidence: 99%
“…29 Furthermore, with regard to the precise prognostic value of TOP2A expression, the existing evidence base is mixed with numerous conflicting results. 7,25,29,34,37,38 Qiao et al 25 reported a subgroup analysis, which demonstrated no significant differences in overall survival or DFS between TOP2A-positive and TOP2A-negative groups in patients with breast cancer. However, Brase et al 34 reported that TOP2A expression was significantly associated with the metastasis-free interval and complete remission in patients with breast cancer.…”
mentioning
confidence: 99%
“…As such it has been widely investigated for potential applications in breast cancer detection and management. 7,8 Anthracyclines are one of the most effective cytotoxic agents used in the treatment of breast cancer patients and inhibit TOP2A by trapping the DNA strand intermediates, leading to persistent DNA cleavage. 8 However, data supporting a potential predictive role for TOP2A status and its sensitivity are mixed.…”
mentioning
confidence: 99%
See 2 more Smart Citations